Beneath the Black Sun of Cabinda - Everson, Vanessa (African Sun Media, 2015)
The story opens at a time when Cabinda - a small African enclave surrounded by the Congo and the Democratic Republic of the Congo, and separated from Angola by the Congo River - is plunged into bloody war. Deep in the heart of Cabinda is the Mayombe rainforest, home to a group of guerrilla fighters whose very existence is to liberate their land from the terrors perpetrated by the Angolan army. Against that backdrop of massacres and deforestation and written with crusading fervour, this novel is much more than a political tract. It is a powerful story of impossible love: the poignant love of the principled, young doctor Albino for the country lass Maria; the redemptory love which his ailing, ruthless grandfather Santos is surprised to feel as death approaches; and the love of a dispossessed people for the land of their birth. Recommended reading, then, for lovers of African literature, as well as for scholars and adepts of colonial and postcolonial literature.